Retrospective, Multicenter Comparison of the Clinical Presentation of Patients Presenting With Diplopia From Giant Cell Arteritis vs Other Causes. Issue 1 (March 2019) - Ross, Ahmara G.; Jivraj, Imran; Rodriguez, Geoffrey; Pistilli, Maxwell; Chen, John J.; Sergott, Robert C.; Moster, Mark; Sheldon, Claire A.; Liu, Grant T.; Foroozan, Rod; Ko, Melissa W.; Francis, Courtney E.; et al.
Abstract : Background: Although giant cell arteritis (GCA) is a well-known cause of transient and permanent vision loss, diplopia as a presenting symptom of this condition is uncommon. We compared symptoms and signs of patients presenting with diplopia from GCA to those from other causes. Methods: This was a multicenter, retrospective study comparing the clinical characteristics of patients presenting with diplopia from GCA with age-matched controls. Demographic information, review of symptoms, ophthalmic examination, and laboratory data of biopsy-proven patients with GCA were compared with those of age-matched controls presenting with diplopia. Results: A total of 27 patients presented with diplopia from GCA, 19 with constant diplopia, and 8 with transient diplopia. All patients with constant diplopia from GCA were matched with 67 control subjects who had diplopia from other etiologies. Patients with GCA were more likely to describe other accompanying visual symptoms (58% vs 25%, P = 0.008), a greater number of systemic GCA symptoms (3.5, GCA vs 0.6, controls, P < 0.001) such as headache (94% [17/18] vs 39% [23/67]; P < 0.001), jaw claudication (80% [12/15] vs 0% [0/36]; P < 0.001), and scalp tenderness (44% [7/16] vs 7% [3/43]; P < 0.001). Ocular ischemic lesions (26% vs 1%, P < 0.001) were also common in patients with diplopia from GCA. Inflammatory markers were elevated significantly in patients with GCA vs controls (erythrocyte sedimentation rate: 91% [10/11] vs 12% [3/25], P < 0.001; C-reactive protein: 89% [8/9] vs 11% [2/19], P < 0.001). Conclusions: GCA is a rare but serious cause of diplopia among older adults and must be differentiated from other more common benign etiologies. Our study suggests that most patients with diplopia from GCA have concerning systemic symptoms and/or elevated inflammatory markers that should trigger further work-up. Moreover, careful ophthalmoscopic examination should be performed to look for presence of ocular ischemic lesions in older patients presenting with acute diplopia.